Managerial Allocation of Time and Effort: The Effects of Interruptions - Seshadri, Sridhar; Shapira, Zur (Management Science, 2001)
Time is one of the more salient constraints on managerial behavior. This constraint may be very taxing in high-velocity environments where managers have to attend to many tasks simultaneously. Earlier work by Radner (1976) proposed models based on notions of the thermostat or “putting out fires” to guide managerial time and effort allocation among tasks. We link these ideas to the issue of the level of complexity of the tasks to be attended to while alluding to the sequential versus parallel modes of processing. We develop a stochastic model to analyze the behavior of a manager who has to attend to a few short-term processes while attempting to devote as much time as possible to the pursuit of a long-term project. A major aspect of this problem is how the manager deals with interruptions. Different rules of attention allocation are proposed, and their implications to managerial behavior are discussed.